Polar microwave brightness temperatures from Nimbus-7 SMMR : time series of daily and monthly maps from 1978 to 1987 - Comiso, Josefino C.; Zwally, H. Jay. (Washington, D.C. : National Aeronautics and Space Administration, Office of Management, Scientific and Technical Information Division, 1989)
Includes bibliographical references (p. 19-20). Mode of access: Internet.